Human-Gorilla and Gorilla-Human: Dynamics of Human-animal boundaries and interethnic relationships in the central African rainforest - Takanori Oishi (Revue de Primatologie)
This paper (1) describes the perceptions of the western lowland gorilla (Gorilla gorilla gorilla) by forest dwellers of southeastern Cameroon and (2) investigates the sociocultural dimension of human–gorilla relationships focusing on folk theories of human–animal hybrids in which the gorilla is deeply embedded, enabling us to deal with the symbolic and social aspects of hunter-gatherer–farmer relations. The Baka hunter-gatherers of the southeast Cameroon–Congo border regions live with their Bakwele farming neighbors. They regard the Bakwele as gorilla–humans that may be reincarnated as gorillas after death. Conversely, the Bakwele regard the Baka as animal–humans that can transform themselves into various animals to raid crops, and believe that there are human–gorillas (dzil-elizaliza) in the wild gorilla population whose bodies are gorilla but whose spirits are those of human beings. There are two types of dzil-elizaliza: the revenant human-gorilla of the deceased, which is gentle and tranquil; and the witch-transformed human-gorilla, which is dangerous, malicious, and harms people. The dual nature of dzil-elizaliza expresses a contrast between the witch-controlled man-eater and the warm-hearted reincarnated ancestral relative in a human-gorilla. Ambivalent representations of dzil-elizaliza also seem to reflect variation of Bakwele’s self-image.Thus, Bakwele and gorillas can be said to share common properties which circulate across a human-nature landscape in the form of a human-animal hybrid. Local narratives of the human–gorilla demonstrate that gorillas are not only the subject of cultural construction that reflects specific people’s sociocultural conditions, but that they are also actors that sometimes intervene in actual social relationships. Here human and gorilla interactions are bidirectional. Much beyond food or symbols for humans, gorillas are human’s ontological counterparts. In this system, gorillas occupy a unique position that crosses both the interethnic boundaries between the Baka and the Bakwele and the interspecies boundaries between humans and animals. From the local people’s worldview, the maintenance of human and gorilla relationships is significant in their cultural practices and the separation of the two species is not desirable. This paper is a revised version of a book chapter published by Oishi, in Japanese in 2012.